Sumienie jako własność i wyróżnik osoby w jej procesie rozwoju - Wrońska, Katarzyna (Horyzonty Wychowania, 2017)
The presented text is an attempt to understand the sense of conscience through the description of its manifestations in the whole dynamics of development, adolescence, upbringing, and also going astray, regression and suppression throughout person’s life as well as in the entirety of his experiences. The phenomenon of conscience revealing itself in the direct experience as a „voice”, „talking” with warning or accusation because of the intended or already done evil turns out to be pain, complaint, suffering of the heart because of the damage or failure to do good. When undertaken (heard) by a person, it can prompt reflection and willingness to improve one’s life, since it creates, together with the whole sphere of cognitive experiences and will, moral awareness. The voice of conscience requires, as its foundation, cognitive acts of awareness and the knowledge of good and evil built in this manner, of moral obligations and one’s own attitude towards them, the ability to formulate judgements concerning one’s own actions and other people, as well as theability to translate general moral principles and use them in a particular situation. It also requires a general insight into values an axiological sensitivity.